Association between vitamin D status and cardiometabolic risk factors in adults with type 2 diabetes in Shenzhen, China - Liu, Yan-Jing; Duan, Jing-Wen; Lu, Dong-Hui; Zhang, Fan; Liu, Hong-Li (Frontiers in Endocrinology, 2024)
Background Evidence of vitamin D status and cardiometabolic health in adults with type 2 diabetes mellitus (T2DM) is still limited. This study aimed to investigate the association between vitamin D status and cardiometabolic risk factors among adults with T2DM in Shenzhen, China. Methods This cross-sectional study included 164 adults (aged ≥18 years) with T2DM who were hospitalized at Peking University Shenzhen Hospital from March 1, 2023, to May 31, 2023. Serum 25-hydroxyvitamin D [25(OH)D] concentration, the active marker of vitamin D, and three major cardiometabolic risk factors including blood pressure (BP), glucose metabolism-related indicators, and blood lipid profiles were collected. Vitamin D deficiency (VDD) was defined as 25(OH)D < 20 ng/mL. Correlation, Regression, and Logistic analysis were applied to verify the association among serum 25(OH)D concentration, VDD, and 11 cardiometabolic risk factors. Results Median 25(OH)D concentration was 21.78 [interquartile range (IQR)=17.51-28.05] ng/mL. The prevalence of VDD was 40.24%. Serum 25(OH)D concentration was significantly negatively correlated with diastolic BP (DBP) and glycated hemoglobin A1c (HbA1c) rather than systolic BP, plasma glucose, plasma C-peptide, and blood lipid profiles among adults with T2DM in both correlation and linear regression analysis. Furthermore, the adjusted odd ratio for poor DBP control (≥90 mmHg) of T2DM patients with VDD was 3.164 (95% confidence interval=1.303, 7.683; P=0.011) compared to those without VDD. Conclusion In China, VDD was highly prevalent among adults with T2DM and associated with greater cardiovascular risk factors, especially with increased chances of uncontrolled DBP. These findings suggest that vitamin D levels should be monitored in T2DM patients, especially those with high DBP.